PERLINDUNGAN HUKUM KETENAGAKERJAAN TERHADAP TENAGA KERJA ANAK YANG BEKERJA DI LUAR HUBUNGAN KERJA PADA BENTUK PEKERJAAN TERBURUK. - Charda, Ujang (Syiar Hukum, 2010)
Laws Number 13 Year 2003 have arranged legal protection to child labour from of the worst forms by focus at child labour trussed a relation work, while for child labour of outside relation work formally not yet been protected maximal, because awaiting Governmental Regulation as a technical guide in prevention, protection and its abolition. For the reason in straightening of labour law in order to legal protection to child labour have to pay attention to regulation factor of legislations, enforcer law and sense of justice of society which structurally, substantial and cultural represent one system union which must walk by synergic and systematical paid attention toly is knowledge of law, understanding of law, behavioral pattern and attitude socialize as indicator in implementation programme protection action law to child labour from of the worst form.